THE ASSOCIATION OF SERUM PROLACTIN LEVELS WITH DISEASE ACTIVITY IN THE PATIENTS WITH RHEUMATOID ARTHRITIS AND SYSTEMIC LUPUS ERYTHEMATOSUS - Cahit Kaçar; Erdal Gilgil; Tiraje Tuncer (Archives of Rheumatology, 2002)
Hormonal factors are blamed in the etiopathogenesis of both rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). Prolactin (PRL) is supposed to be amongst those factors. The aim of this study is to investigate the association of serum PRL levels with disease activity of RA and SLE. Twenty-five patients with RA and 14 patients with SLE and 16 healthy controls for RA and 10 healthy controls for SLE, matched for age and sex, were enrolled in the study. Blood samples were drawn from the all participants in the morning for the analysis of PRL and other relevant laboratory measures. Disease activity in the patients with RA was determined by tender joint score, swollen joint count, pain assessment by visual analogue scale (VASpain), duration of morning stiffness, erythrocyte sedimentation rate and C-reactive protein (CRP) levels. Disease activity in the SLE patients was evaluated by SLE disease activity index (SLEDAI). PRL levels were higher in the RA group(p<0.05). Hyperprolactinemic patients with RA showed higher CRP and rheumatoid factor levels, VASpain and tender joint scores compared to normoprolactinemic RA patients (p<0.05) and mean age of hyperprolactinemic RA patients was significantly lower than of the normoprolactinemic ones. No association was found between SLEDAI and PRL. It is suggested that PRL plays a role in the pathogenesis of RA and is associated with disease activity in those patients. As PRL has no associaton with SLE, it can be hypothesized that SLE and RA should have different etiopathogenetic profiles.